'Doublecheck: a sensory confirmation is required to own a robotic hand, sending a command to feel in charge of it'. Issue 4 (1st October 2020) - Pinardi, M.; Ferrari, F.; D'Alonzo, M.; Clemente, F.; Raiano, L.; Cipriani, C.; Di Pino, G.
ABSTRACT: Over a lifetime of experience, the representation of the body is built upon congruent integration of multiple elements constituting the sensorimotor loop. To investigate its robustness against the rupture of congruency between senses and with motor command, we selectively manipulated in healthy subjects the binds between sight, proprioception, and efferent motor command. Two experiments based on the Moving Hand Illusion were designed employing Tendon Vibration Illusion to modulate proprioception and generate illusory altered feedback of movement. In Experiment A, visuomotor congruency was modulated by introducing adelay between complex multifingered movements performed by arobotic hand and real movement of each participant's hand. In the presence of the motor command, visuomotor congruency enhanced ownership, agency, and skin conductance, while proprioceptive-motor congruency was not effective, confirming the prevalence of vision upon proprioception. In Experiment B, the impact of visuo-proprioceptive congruency was tested in the absence of motor command because the robotic hand moved autonomously. Intersensory congruency compensated for the absence of motor command only for ownership. Skin conductance in Exp Band Proprioceptive Drift in both experiments did not change. Results suggest that ownership and agency are independently processed, and presence of the efferent component modulates sensory feedbacks salience. The brain seems to require the integration of at least two streams of congruent information. Bodily awareness can be generated from sensory information alone, but to feel in charge of the body, senses must be double-checked with the prediction generated from efference copy, which is treated as an additional sensory modality.